Race: Tradition and convenience, or taxonomic reality? More on the race concept in Polish anthropology - Kaszycka, Katarzyna A.; Strzałko, Jan (Anthropological Review, 2003)
Against the background of the race debate and the principal elements of the current understanding of human intraspecific variation, we present the status of the race concept in Polish anthropology. Using questionnaires, we twice surveyed physical anthropologists about their agreement with the statement “There are biological races within the species Homo sapiens.” In the 1999 study, 62% of respondents disagreed with race (defined as subspecies) and 31% accepted it. In the 2001 study, this proportion was reversed: only 25% rejected race (by any definition) with the remaining respondents (75%) differing widely as to its accepted meaning. Each time, age was significant factor in differentiating the replies – in general, acceptance of race increased with age while rejection declined. It appears that Polish anthropologists regard race as a term without taxonomic value and often in a populational sense. Here we point out, however, the risks associated with the “metaphorical” use of the term “race”, as it relativizes the essential error of perceiving the existence of subspecific taxa within our species.